2021
DOI: 10.1101/2021.08.30.458252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of non-linear competitive interactions on quantifying niche and fitness differences

Abstract: The niche and fitness differences of modern coexistence theory separate mechanisms into stabilizing and equalizing components. Although this decomposition can help us predict and understand species coexistence, the extent to which mechanistic inference is sensitive to the method used to partition niche and fitness differences remains unclear. We apply two alternative methods to assess niche and fitness differences to four well known community models. We show that because standard methods based on linear appro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…1, red block). These equations have been applied to similar community models, by rephrasing these similar community models in the terms of the inter and intra-specific interaction coefficients α ij (Spaak et al 2021a). Specifically, this method has been used in community models including competition for predators (Chesson and Kuang 2008) or mutualists (Johnson 2021), a time discrete annual plant model (Godoy and Levine 2014), resource competition models with Holling type II response (Letten et al 2017), inclusion of facilitation between species (Bimler et al 2018) and plant-soil feedbacks (Kandlikar et al 2019).…”
Section: Review Of Niche and Fitness Differences Methodsmentioning
confidence: 99%
“…1, red block). These equations have been applied to similar community models, by rephrasing these similar community models in the terms of the inter and intra-specific interaction coefficients α ij (Spaak et al 2021a). Specifically, this method has been used in community models including competition for predators (Chesson and Kuang 2008) or mutualists (Johnson 2021), a time discrete annual plant model (Godoy and Levine 2014), resource competition models with Holling type II response (Letten et al 2017), inclusion of facilitation between species (Bimler et al 2018) and plant-soil feedbacks (Kandlikar et al 2019).…”
Section: Review Of Niche and Fitness Differences Methodsmentioning
confidence: 99%
“…The relative importance of different coexistence mechanisms might depend on species richness. For example, Spaak et al (2021a) have shown that increasing species richness increases the importance of fitness differences compared to niche differences. Third, the trophic structure was simple and excluded any higher trophic level and any mixotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…These communities behaved similarly to communities driven by Allee effects or communities driven by obligatory mutualism. It was not previously recognized that these communities can arise from simple resource competition, a well understood mechanism that is key for modern coexistence theory (Chesson & Kuang, 2008; Chesson, 1990; Letten et al ., 2017; Letten & Stouffer, 2019; Spaak et al ., 2021a,b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations